Haptoglobin genotype is a risk factor for coronary artery disease in prediabetes: A case-control study - Emily Kate Mewborn; Elizabeth Ann Tolley; David Bruce Wright; Amy Lynn Doneen; Margaret Harvey; Ansley Grimes Stanfill (Elsevier, 2024)
Objective: Coronary artery disease (CAD) prediction remains inconsistent with many unappreciated risk factors. Haptoglobin genotype determines the haptoglobin protein's effectiveness to bind free hemoglobin and prevent oxidative stress, a contributor to atherosclerosis. The haptoglobin 2-2 genotype increases the prevalence of cardiovascular disease (CVD) approximately five times compared to the 1-1 genotype in individuals with diabetes. The risk is unknown in prediabetes. The purpose of this study was to determine an association between haptoglobin genotype and CAD in prediabetes. Methods: The researchers used case-control convenience sampling from two cardiovascular disease prevention clinics in Memphis, TN, and Spokane, WA, from January 1, 2016 to March 31, 2020. Participants were ages 35-70, had prediabetes, and free of chronic inflammatory or infectious diseases. Cases had a history of subclinical or clinical CAD, while controls did not have a history of CAD. Differences between cases and controls and among haptoglobin genotypes were analyzed using t-tests and ANOVA for continuous variables and chi-square or Fisher's exact tests for categorical variables. Associations among Hp genotypes and CAD were estimated using logistic regression. Results: The sample (N = 178; 72 cases and 106 controls) was 96 % white and 64 % male. Cases had lower total cholesterol (p = 0.0001) and high-sensitivity C-reactive protein (p = 0.021). Except for CAD, haptoglobin genotype was independent of any demographic or clinical variable. Haptoglobin 2-2 genotype had 4.0 times higher odds of CAD than haptoglobin 1-1 (p = 0.01). Conclusion: Haptoglobin 2-2 genotype had approximately four times higher odds of having CAD compared to the haptoglobin 1-1 genotype. Cases had more desirable clinical profiles, likely attributable to more aggressive treatment of traditional risk factors than controls. Haptoglobin genotype is a potentially important CAD risk factor in prediabetes (88 million Americans). Further studies are needed for interventions to reduce the oxidative stress associated with the Hp 2-2 genotype and glycosylated hemoglobin and for CAD reduction.